Regionalização da saúde no oeste de Mato Grosso : um estudo de caso do colegiado de gestão regional - Silva, Maria José Vieira da (2014)
This thesis aimed to analyze the regional health management that was developed by the Regional Management Collegiate of Mato Grosso, considering the guidlines of the Pact by Health during the period from 2010 to 2012. The study was based on the analyzes of federative system and on the intergovernamental relations and also on concepts adopted for the analyses of management and the regionalization of the health, such as institutionality and governance. The methodological approach eminently qualitative was developed through the case study where was sought to understand the social phenomena that happen in a decisive stage of sus. The techniques of data collection were the interview, the observation, the questionary self applied and the documental analysis. For the treatment of the qualitative data, the content analysis was used. The politic of regionalization estabilished by SES/MT during the period from 1995 to 2002 underwent a process of discontinuity and although these regionalised instances kept on going they were weak before a moviment of recenter promoted by the State Secretariat. The Regional Management Colligiate was classified as intermediate. It is found formaly established and organized but do not have a sufficient structure in order to have a proper functioning. It is a valued place for its actors that are representative. Its legitimacy as a place of negociation and technical, political ruling concerns are relative. Political and party interfernce are present in the deliberative process. In relation to the Regional Management was identified that the autonomy and the capacity of the Colligiate of formulation, implementation and the political evaluation and regional planning is limited. The Colligiate is constituted as instancy of regional governance demanding the strenthering of its political, managerial and financial autonomy.